Aus dem Literaturerbe in die Sprachwissenschaft - Groenke, Ulrich (Folia Scandinavica Posnaniensia, 2007)
In medieval studies the term „literaturę" covers practically all notions of fictional or artistic and factual or scientific writing. Works of totally different kinds of literaturę may be found united in a compilation sharing literary fame though not materiał comprehension. A case in point is the compilation of Snorra Edda and the Grammatical Treatises in the Codex Wormianus. This article sketches the history of understanding and misunderstanding the duality of the pooled texts.